PENGARUH DAYA TANGGAP DAN JAMINAN TERHADAP KEPUASAN PELANGGAN DI PT. SURIATAMA MAHKOTA KENCANA MEDAN CABANG KATAMSO - Khomeiny Yunior (Universitas Islam Islam Sumatera Utara, 2020)
PT. Suriatama Mahkota Kencana is a company engaged in supermarkets located at Jalan Brigjen Katamso, No. 710 Kampung Baru, Medan. There were several things thatneeded to be considered in this company related to customer complaints such as dimensions of responsiveness and guarantees at PT. Suriatama Mahkota Kencana. This study used several theories related to responsiveness, assurance and customer satisfaction. This research used a quantitative approach, this type of research was descriptive quantitative, and the nature of this research was descriptive explanatory. Data collection was performed by interviews, questionnaires, and documentation. Data analysis method used was multiple regression. The populations of this study were 175 respondents who were customers who did shopping individually. For the sample test, 122 respondents were selected based on the individual criteria, of which 30 respondents were taken from the rest of the population for the validity test. The results of the research on the hypothesis showed that partially, responsiveness and assurance had a significant effect on customer satisfaction and simultaneously the responsiveness and assurance had a significant effect on customer satisfaction. The calculation of coefficient of determination was 0,502 which means customer satisfaction could be explained by the variables of responsiveness and guarantee reaching up to 50.2%. This study concludes that there was a significant effect simultaneously and partially (individually) between the responsiveness or assurance of on customer satisfaction at PT. Suriatama Mahkota Kencana Medan branch of Katamso